Thymectomy immediately after myasthenic crisis - Martić, Vesna; Marić, Nebojša; Djordjević, Dragan (Vojnosanitetski pregled, 2021)
Introduction. Myasthenic crisis (MC) refers to rapid progression of myasthenic weakness accompanied by ventilatory and bulbar dysfunction. Since there is no single standard accepted in the treatment of every patient in myasthenic crisis, we report our experience in the treatment of such a patient. Case report. We report a 22-year-old male patient with clinical, pharmacological, neurophysiological, and immunological diagnosis of seropositive generalized myastenia gravis (MG) of unstable course. During the first 6 months of his disease, three deteriorations were registered, and the last one developed into a myasthenic crisis. The patient was intubated. Previous anticholinergic and imunosuppresive therapies were withdrawn, and he was treated with plasma exchange and human immunoglobulins during the crisis. After thymectomy, performed 3 weeks after extubation, the patient was stable. Conclusion. Progress in treatment of MC over the last few decades has dramatically improved its prognosis. Thymectomy is useful in the prevention of MC recurrence.